L-Arginine in Clinical Nutrition - Patel, Vinood B.; Preedy, Victor R.; Rajendram, Rajkumar (Springer International Publishing : Imprint: Humana Press, 2017)
This text presents the application of current nutritional knowledge by physicians and incorporates emerging fields of science and important discoveries. Written by authors of international and national standing, leaders in the field and trendsetters, Arginine in Clinical Nutrition is essential reading for nutritionists and dietitians, public health scientists, doctors, epidemiologists, health care professionals of various disciplines, policy makers and marketing and economic strategists.
Keywords: Medicine.; Nutrition.; Clinical nutrition.; elektronické knihy; electronic books